2011
DOI: 10.1021/ol200770k
|View full text |Cite
|
Sign up to set email alerts
|

Virgatolides AC, Benzannulated Spiroketals from the Plant Endophytic Fungus Pestalotiopsis virgatula

Abstract: Virgatolides A-C (1-3), unique metabolites with a 3',4',5',6'-tetrahydrospiro[chroman-2,2'-pyran] core, were isolated from cultures of the plant endophytic fungus Pestalotiopsis virgatula. Compounds 1-3 possess two previously undescribed skeletons originating from a benzannulated 6,6-spiroketal and one (2 and 3) and two (1) γ-lactone units, respectively. The structure of 1 was secured by X-ray crystallography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 30 publications
2
35
0
9
Order By: Relevance
“…A 6,6-spiro-ring system was constructed in consideration of the 13 C chemical shift value of C-15 at 101.9 p.p.m. [14][15][16][17][18][19] and the hydrogen deficiency index of 5, which was also confirmed by the correlations between H-12 and 14-Me, between H-17 and H-19 and between 14-Me and H-16eq in the ROESY spectrum (Supplementary Figure S7). These ROESY correlations suggested that the conformation around C-15 was restricted and they formed spiro-fused tetrahydropyrans.…”
Section: Resultssupporting
confidence: 54%
“…A 6,6-spiro-ring system was constructed in consideration of the 13 C chemical shift value of C-15 at 101.9 p.p.m. [14][15][16][17][18][19] and the hydrogen deficiency index of 5, which was also confirmed by the correlations between H-12 and 14-Me, between H-17 and H-19 and between 14-Me and H-16eq in the ROESY spectrum (Supplementary Figure S7). These ROESY correlations suggested that the conformation around C-15 was restricted and they formed spiro-fused tetrahydropyrans.…”
Section: Resultssupporting
confidence: 54%
“…Compound 2 was obtained as a yellow oil, and its molecular formula was determined to be C 13 C NMR spectrum showed one methoxyl carbon at d C 60.9, three methyls at d C 18.0, 11.3, and 10.6, six carbon signals belonging to the arhamnose moiety at d C 106.4, 73.5, 72.4, 72.2, 72.0, and 18.0. The structure assembly of 2 was mainly achieved using the HMBC experiment.…”
Section: Resultsmentioning
confidence: 99%
“…32 exhibits moderate antifungal properties, with a minimum inhibitory concentration of approximately 10 g/mL to Pythium ultimum, and antioxidant activity 11 times greater than the vitamin E derivative trolox. Photinides A-F (33)(34)(35)(36)(37)(38), six new unique benzofuranone-derived -lactones, and a known compound 6-methoxy-9-methyl-4'-hydroxyaurone (39) have been isolated [19] …”
Section: Benzofuranonesmentioning
confidence: 99%
“…Virgatolides A-C (127-129), unique metabolites with a 3 , 4 , 5 , 6 -tetrahydrospiro [chroman-2, 2 -pyran]core, were isolated [39] from cultures of the plant endophytic fungus P. virgatula. 127-129 possess two previously undescribed skeletons originating from a benzannulated 6, 6-spiroketal and one (128 and 129) and two (127) -lactone units, respectively, and showed modest cytotoxicity against HeLa cells, with IC50 values of 19.0, 22.5, and 20.6 M, respectively.…”
Section: Spiroketal Compoundsmentioning
confidence: 99%